THE EFFECTIVENESS OF THE KEMBAQ MODULE IN DEVELOPING ARABIC WRITING PROFICIENCY AMONG SECONDARY SCHOOL LEARNERS - Ramlan, Muhammad Fikri; Mohd Ismath, Nurul Hanilah (KORİNT Yayıncılık, 2025)
This paper investigates the effectiveness of the instructional unit KEMBAQ in enhancing Arabic writing skills among students at MRSM Ulul Albab, Felda Trolak, Malaysia. Although Arabic has been part of their curriculum for several years, students still face persistent challenges in producing coherent sentences and essays. The study employed a quantitative analytical method with a sample of 208 first- and second-year students participating in the Arabic Camp program. Research instruments included questionnaires and pre- and post-tests, with data analyzed using SPSS. Findings revealed that students’ writing proficiency was generally weak before the intervention but improved significantly after the implementation of KEMBAQ. The module helped learners move beyond memorization toward independent writing by simplifying grammar rules and providing structured practice. The paper concludes that KEMBAQ is an effective tool for teaching Arabic writing and should be integrated into secondary-level curricula to strengthen student performance and foster learner autonomy.